A Long-Run Structural Macroeconometric Model for Germany: An Empirical Note - Pu Chen; Elena Schneider; Joachim Frohn (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
To provide an modelling strategy with transparent and theoretically coherent foundation has been one of the targets of the paper by Garratt, Lee, Pesaran and Shin. They develop a core model for a small open economy based production technology, arbitrage conditions, flow identities and long-run solvency conditions. This leads to five long-run relations: the uncovered interest rate parity, the purchasing power parity, production function, trade balance and real money balance. Since the economic theory there is formulated generally but not restricted to the economy of UK for which their empirical model is implemented, we expect that this modelling strategy should be able to generate similar results for the data of other countries. In this empirical note we apply the modelling strategy to German data to see in how far the economic theory formulated there can account for German data. We are able to identify five cointegration relations in a conditional vector error correction model and the overidentification restrictions of the five cointegration relations as, UIP, PPP, production function, trade balance and real money balance are not rejected by the data.
Keywords: C32; E24; 330; Long-Run Structural VAR; Macroeconomic Modelling; Ökonometrisches Makromodell; VAR-Modell; Strukturgleichungsmodell; Offene Volkswirtschaft; Mineralölpreisschock; Deutschland